2009
DOI: 10.1590/s0102-86502009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Simplified correction of a meningomyelocele-like defect in the ovine fetus

Abstract: Purpose: To develop a simplified technique for antenatal correction of a meningomyelocele -like defect in fetal sheep to allow direct skin closure. Methods: A spinal defect was surgically created at 75 days of gestation in the fetuses of 36 pregnant sheep, 23 survived the surgery. At 102 days gestation, the defect was corrected in 14 cases (9 were left untreated). Skin surrounding the defect was dissected below the dermis to permit its edges to be approximated and sutured, without interposing any material to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“…Six weeks after ethanol injection in femoral head of the ovines through the core decompression technique Manggold et al 8 found most severely damaged areas in the femoral head, and bone regeneration occurred in twelve weeks after induction. Therefore, we chose perform the transplantation of stem cells six weeks after ONFH induction, and evaluate the cell therapy result 10 weeks after induction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six weeks after ethanol injection in femoral head of the ovines through the core decompression technique Manggold et al 8 found most severely damaged areas in the femoral head, and bone regeneration occurred in twelve weeks after induction. Therefore, we chose perform the transplantation of stem cells six weeks after ONFH induction, and evaluate the cell therapy result 10 weeks after induction.…”
Section: Discussionmentioning
confidence: 99%
“…Although some relevant clinical data on cellular therapy for ONFH exist 8,16,17,27 , it remains unknown how many of these cells actually participate in the bone reparation and engraftment process and how many survive and proliferate in the center of the femoral head, after the transplant. This observation has also been made by others 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in order to allow endoscopic approach, the surgical technique to correct the defect itself was simplified. The success of this new simplified technique was previously demonstrated in rabbits (8) and sheep (9) . The classic neurosurgical procedure, which was used for the correction of the defect in the MOMS study, consists in closing the defect in different planes.…”
Section: Introductionmentioning
confidence: 87%
“…Biosynthetic cellulose was tested as dura mater substitute in dogs submitted to craniotomy by Mello et al (18) , and it was found that it induced the formation of neo-dura mater. Our group tested cellulose for the correction of a spinal defect in rabbit fetuses (8) , and later in sheep fetuses (9,20) , and showed that this material did not cause foreign-body reactions and that it also led to the formation of a neo-dura mater, preventing adhesion between the scar and the medulla. In these studies the cellulose was placed over the medulla, and no stitches or adhesive substances were used for fixation; only the skin was closed over the cellulose patch to maintain it over the medulla.…”
Section: A D B E C Fmentioning
confidence: 99%